Frontline Science: CXCR7 mediates CD14+CD16+ monocyte transmigration across the blood brain barrier: a potential therapeutic target for NeuroAIDS. Issue 5 (1st November 2017) - Veenstra, Mike; Williams, Dionna W; Calderon, Tina M; Anastos, Kathryn; Morgello, Susan; Berman, Joan W
Abstract : CXCR7 is expressed on CD14 + CD16 + monocytes in PBMC from uninfected and HIV infected individuals; CCX771 specifically blocks CXCL12-mediated transmigration of these cells. Abstract: CD14 + CD16 + monocytes transmigrate into the CNS of HIV-positive people in response to chemokines elevated in the brains of infected individuals, including CXCL12. Entry of these cells leads to viral reservoirs, neuroinflammation, and neuronal damage. These may eventually lead to HIV-associated neurocognitive disorders. Although antiretroviral therapy (ART) has significantly improved the lives of HIV-infected people, the prevalence of cognitive deficits remains unchanged despite ART, still affecting >50% of infected individuals. There are no therapies to reduce these deficits or to prevent CNS entry of CD14 + CD16 + monocytes. The goal of this study was to determine whether CXCR7, a receptor for CXCL12, is expressed on CD14 + CD16 + monocytes and whether a small molecule CXCR7 antagonist (CCX771) can prevent CD14 + CD16 + monocyte transmigration into the CNS. We showed for the first time that CXCR7 is on CD14 + CD16 + monocytes and that it may be a therapeutic target to reduce their entry into the brain. We demonstrated that CD14 + CD16 + monocytes and not the more abundant CD14 + CD16 − monocytes or T cells transmigrate to low homeostatic levels of CXCL12. This may be a result of increased CXCR7 on CD14 + CD16 + monocytes. We showed that CCX771 reduced transmigration of CD14 + CD16 + monocytes but not of CD14 + CD16 − monocytes from uninfected and HIV-infected individuals and that it reduced CXCL12-mediated chemotaxis of CD14 + CD16 + monocytes. We propose that CXCR7 is a therapeutic target on CD14 + CD16 + monocytes to limit their CNS entry, thereby reducing neuroinflammation, neuronal damage, and HIV-associated neurocognitive disorders. Our data also suggest that CCX771 may reduce CD14 + CD16 + monocyte-mediated inflammation in other disorders.